Diagnostic devices with microfluidics - Piraino, Francesco; Selimović, Šeila (Devices, circuits, and systems., 2017)
"This book provides a current view of the research and commercial landscape of diagnostics devices, particularly those that utilize microscale technologies, intended for both patient and laboratory use. Common diagnostic devices that are based on microfluidic principles include glucose sensors for diabetic patients and over-the-counter pregnancy tests. Other diagnostic devices are being developed to quickly test a patient for bacterial and viral infections, and other diseases. The chapters, written by experts from around the world, discuss how to fabricate, apply, and market microfluidic diagnostic chips ́-- for lab and at-home use. Most importantly, the book also contains a discussion of topics relevant to the private sector, including patient-focused, market-oriented development of diagnostics devices."--Provided by publisher.